Matriarchy, matriality and patriarchal Illusion: elements for a science from earth : Matriarchy, matriality and patriarchal Illusion: elements for a science from earth - GUERRERO OSORIO , Arturo (Utopía y Praxis Latinoamericana, 2022)
Patriarchy is historical. To transcend the society and science that emerged within it, it is necessary to broaden the gaze, and take a journey from our primate ancestors and the organizational heritage that our species continued most of its experience, as the sustenance of a very probable Paleolithic matriarchal order whose transformation would have created the conditions of possibility for the emergence of the Patriarchal Illusion. And appreciate, in this intersection, matriality as a source to reinvent ourselves in the present and generate a civilizing proposal and post-patriarchal knowledge.